2010
DOI: 10.1051/0004-6361/201014232
|View full text |Cite
|
Sign up to set email alerts
|

Is BL Lacertae an “orphan” AGN?

Abstract: Aims. We have analysed optical spectra of BL Lacertae, the prototype of its blazar subclass, to verify the broad Hα emission line detected more than a decade ago and its possible flux variation. We used the spectroscopic information to investigate the question of the BL Lacertae parent population. Methods. Low-and high-resolution optical spectra of BL Lacertae were acquired with the DOLORES spectrograph at the 3.58 m telescopio nazionale Galileo (TNG) during four nights in [2007][2008], when the source was in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 67 publications
0
34
0
Order By: Relevance
“…As discussed in the present paper and in Raiteri et al (2009), the amount of this excess strongly depends on both the Galactic extinction and instrument calibration, but it is not easy to cancel it out completely. In any case, Capetti et al (2010) showed that after twelve years from the first detection of the Hα broad emission line by Vermeulen et al (1995) and Corbett et al (1996, see also Corbett et al 2000, the Hα line is still there, even more luminous than before. This suggests that a disc is also there to photoionise the broad line region.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…As discussed in the present paper and in Raiteri et al (2009), the amount of this excess strongly depends on both the Galactic extinction and instrument calibration, but it is not easy to cancel it out completely. In any case, Capetti et al (2010) showed that after twelve years from the first detection of the Hα broad emission line by Vermeulen et al (1995) and Corbett et al (1996, see also Corbett et al 2000, the Hα line is still there, even more luminous than before. This suggests that a disc is also there to photoionise the broad line region.…”
Section: Discussionmentioning
confidence: 92%
“…We notice that the source redshift is z = 0.0686 (Vermeulen et al 1995) and hence the broad Hα emission line enters the tails of the R and I passbands. However, referring to Capetti et al (2010), one can estimate that its flux contribution is only a few thousandths of that of the continuum. Hence, the presence of the line cannot affect the variability in these bands, at least when the source brightness is at these levels.…”
Section: Optical and Near-infraredmentioning
confidence: 99%
See 1 more Smart Citation
“…BL Lac has broad H-α and H-β lines (Vermeulen et al 1995) that vary in flux. Capetti et al (2010) found that the broad H-α flux increased by 50% in ten years, which could indicate that the photoionizing radiation field from the accretion disk is variable or that there was an increase in the gas in the broad line region. In BL Lac, the broad line region may be underluminous compared to other AGN (Capetti et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Capetti et al (2010) found that the broad H-α flux increased by 50% in ten years, which could indicate that the photoionizing radiation field from the accretion disk is variable or that there was an increase in the gas in the broad line region. In BL Lac, the broad line region may be underluminous compared to other AGN (Capetti et al 2010). The discovery of even weak broad emission lines in BL Lac means that in some ways, BL Lac itself is more similar to FSRQs than to less luminous BL Lac objects such as Mkn 421 and Mkn 501 (see discussion in Madejski et al 1999).…”
Section: Introductionmentioning
confidence: 99%